High-oxidation-resistance Al2O3-SiC-C tapping channel castable and preparation method thereof

By using tungsten atoms to cover nano-silicon carbide and composite antioxidants in the sulcus pouring pouring in the blast furnace, combined with other components, prepare high antioxidant Al2O3-SIC-C to combine iron gap pouring, solve existing technology, and solve existing technology The problem of insufficient anti -oxidation in China has significantly improved high temperature performance and service life.

CN119350005APending Publication Date: 2025-01-24WUHAN METALLURGY ARCHITECTURE RES YUAN CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411528361.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-24

Smart Images

  • Figure BDA0005109850920000051
    Figure BDA0005109850920000051
  • Figure BDA0005109850920000061
    Figure BDA0005109850920000061
  • Figure BDA0005109850920000062
    Figure BDA0005109850920000062
Patent Text Reader

Abstract

The invention belongs to the technical field of unshaped refractory materials, and discloses an Al2O3-SiC-C tapping channel castable with high oxidation resistance and a preparation method of the Al2O3-SiC-C tapping channel castable. The castable comprises the following components in parts by weight: 45-65 parts of fused brown corundum, 10-20 parts of fused compact corundum, 12-18 parts of silicon carbide 0-1mm, 5-8 parts of activated aluminum oxide micro powder, 1-2 parts of cement, 1.5-2.5 parts of silicon dioxide micro powder, 1-3 parts of tungsten atom coated nano silicon carbide, 1-3 parts of a carbon material, 1-2 parts of metal silicon powder, 1-2 parts of a composite anti-explosion agent, 0.2-0.4 part of a composite antioxidant and 0.1-0.2 part of a composite water reducing agent. The obtained iron runner castable has good high-temperature oxidation resistance, high-temperature slag corrosion resistance and scouring resistance, the production and construction process is simple, and the service life is long.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of castables, and in particular relates to a high-oxidation-resistant Al2O3-SiC-C quality iron tapping ditch castable and a preparation method thereof. Background Art

[0002] With the rapid development of blast furnace smelting technology, blast furnaces at home and abroad have gradually reduced energy consumption and increased pig iron production through high wind temperature and high oxygen enrichment. High wind temperature and high oxygen enrichment can accelerate the reaction speed and improve ironmaking efficiency. At the same time, they can also reduce environmental pollution, reduce the cost per ton of iron, reduce fuel consumption per ton of iron, and improve labor efficiency and environmental benefits.

[0003] The tapping ditch in front of the furnace is the only way for molten iron to flow from the blast furnace to the molten iron ladle. It is in an environment of severe temperature fluctuations caused by intermittent tapping and severe erosion by slag / molten iron for a long time. High wind temperature and high oxygen enrichment will inevitably lead to increased smelting intensity and increased tapping temperature, further deteriorating the use conditions. At present, the refractory material of the tapping ditch of blast furnace mainly adopts Al2O3-SiC-C system. This castable system has good thermal shock resistance and slag resistance, and has become the first choice for refractory materials of the working lining of the tapping ditch of blast furnace. However, Al2O3-SiC-C system contains a large amount of SiC and C. When the tapping ditch is in high temperature conditions, C is easily oxidized and lost, resulting in a sharp decrease in the thermal shock resistance, high temperature resistance and oxidation resistance of the tapping ditch castable; SiC is also easily oxidized to form SiO2 at high temperature, and then reacts with CaO in the slag to form low-melting products, resulting in reduced resistance to molten iron scouring and slag erosion of refractory materials, and greatly reducing the service life of refractory materials. Therefore, the development of refractory materials for the iron-making ditch with excellent high-temperature oxidation resistance has become an important technical issue that needs to be urgently solved in the blast furnace iron-making plant.

[0004] CN117247272 A discloses an anti-oxidation blast furnace iron channel castable and its preparation method. The invention improves the anti-oxidation property of the castable by adding molybdenum strontium powder, andalusite and surface modified carbon black. The main raw material is to use the generated oxide liquid phase to block the pores, block the infiltration of oxygen into the castable, and improve the anti-oxidation property of the castable. However, its main defects are: the process is complicated, the amount of liquid oxide is uncontrollable, and too much liquid phase may be generated, resulting in a decrease in the high-temperature performance of the castable.

[0005] CN117049883 A discloses an anti-oxidation castable for the main iron channel of a blast furnace. The invention utilizes the dispersibility and filling properties of submicron silicon powder to improve the low-temperature oxidation resistance of the castable to a certain extent; and utilizes the characteristics of porous mullite, such as low density, large specific surface area, low thermal conductivity and low thermal expansion coefficient, to improve the thermal shock resistance of the castable to a certain extent. However, its main defects are: (1) Mullite is prone to secondary mullitization at high temperatures, resulting in expansion, which affects the compactness of the castable. (2) If too much SiO2-containing raw material is added, a large amount of liquid phase is easily formed at high temperatures, which affects the high-temperature performance.

[0006] CN111087230A discloses a green, environmentally friendly, high-strength, anti-oxidation, permeable iron channel castable and its preparation method. The invention uses K-type anti-oxidation composite nano-carbon powder to replace spherical asphalt to improve the oxidation resistance of carbon materials, and uses nano-modified wax stone powder to replace pure calcium aluminate cement to reduce the formation of low-melting products, but its main defects are: 1) complex process and high production cost; 2) adding too much nano-superfine powder makes it difficult to disperse; 3) the nano-modified wax stone powder has low bonding strength at room temperature. Summary of the invention

[0007] The purpose of the present invention is to provide a high-oxidation-resistant Al2O3-SiC-C iron tapping ditch castable and a preparation method thereof in view of the defect that the existing iron tapping ditch castable has insufficient high-temperature oxidation resistance. The castable achieves improved oxidation resistance in a high-temperature temperature range above 1400°C, significantly improves the high-temperature slag erosion resistance and scouring resistance of the castable, and has broad application prospects.

[0008] To achieve the above purpose, the technical solution adopted by the present invention is:

[0009] Provided is a highly oxidation-resistant Al2O3-SiC-C quality iron ditch castable, which comprises, by weight, 45-65 parts of fused brown corundum, 10-20 parts of fused dense corundum, 12-18 parts of silicon carbide 0-1mm, 5-8 parts of activated alumina powder, 1-2 parts of cement, 1.5-2.5 parts of silicon dioxide powder, 1-3 parts of tungsten atom-coated nano silicon carbide, 1-3 parts of carbon material, 1-2 parts of metallic silicon powder, 1-2 parts of composite explosion-proof agent, 0.2-0.4 parts of composite antioxidant and 0.1-0.2 parts of composite water reducer.

[0010] According to the above scheme, the fused brown corundum consists of a part with a particle size of 8-5mm, a part with a particle size of 5-3mm, and a part with a particle size of 3-1mm, and the mass ratios thereof are 40-50%, 25-30%, and 25-30% respectively.

[0011] According to the above scheme, the fused dense corundum consists of a part with a particle size of 1 to 0.074 mm and a part with a particle size of ≤0.074 mm, and the mass ratios of the two are 50 to 60% and 40 to 50% respectively.

[0012] According to the above scheme, the silicon carbide 0-1mm consists of a part with a particle size of 1-0.074mm and a part with a particle size of ≤0.074mm, wherein the mass proportions of the part with a particle size of 1-0.074mm and the part with a particle size of ≤0.074mm are 45-55% and 45-55% respectively.

[0013] According to the above scheme, the activated alumina powder d 50 ≤2μm, Al2O3≥99%.

[0014] According to the above scheme, the cement is pure calcium aluminate cement, wherein Al2O3≥68%.

[0015] According to the above scheme, the silicon dioxide fine powder has d50≤5μm and SiO2≥96%.

[0016] According to the above scheme, the tungsten atom-coated nano-silicon carbide uses hexacarbonyl tungsten powder as a precursor, and uses chemical vapor deposition to coat atomic tungsten on the surface of SiC powder to obtain atomic tungsten-coated SiC powder.

[0017] According to the above scheme, in the tungsten atom-coated nano-silicon carbide, the silicon carbide particle size is 400-600nm, and the thickness of the tungsten atom coating layer is 100-200nm.

[0018] According to the above scheme, the carbon material is spherical pitch, carbon black or a mixture of the two.

[0019] According to the above scheme, the particle size of the metal silicon powder is ≤0.44 μm, and the silicon content is ≥98%.

[0020] According to the above scheme, the composite explosion-proof agent includes two or three of metal aluminum powder, aluminum lactate, and explosion-proof fiber. Preferably, the explosion-proof fiber is polypropylene fiber with a length of 2-4 mm.

[0021] According to the above scheme, the composite antioxidant is a mixture of boron carbide and zirconium boride.

[0022] According to the above scheme, the composite water reducer includes two or three of sodium tripolyphosphate, FDN (sodium polymethylene naphthalene sulfonate), and polycarboxylic acid high-efficiency water reducer.

[0023] According to the above scheme, the iron trough castable is prepared by adding tungsten atom-coated nano silicon carbide powder and composite antioxidant into polyethylene glycol solution to obtain mixed slurry, then vacuum spray drying to obtain mixed powder, and then mixing with other remaining components.

[0024] Provided is a method for preparing a highly oxidation-resistant Al2O3-SiC-C iron ditch castable, comprising the following steps:

[0025] 1) Adding tungsten atom-coated nano silicon carbide powder and composite antioxidant into polyethylene glycol solution and stirring to obtain mixed slurry; then vacuum spray drying to obtain dry mixed powder.

[0026] 2) Mix fused brown corundum, fused dense corundum, silicon carbide, activated alumina powder, cement, silicon dioxide powder, carbon material, metallic silicon powder, composite explosion-proof agent, composite water reducing agent and the mixed powder obtained in step 1), and stir evenly to obtain a highly antioxidant Al2O3-SiC-C quality iron ditch castable.

[0027] According to the above scheme, in step 2), stirring is carried out in a forced mixer for 15-30 minutes.

[0028] The present invention provides a highly resistant Al2O3-SiC-C iron ditch castable. The iron ditch castable is located in a key position of a blast furnace and has a great influence on the normal and smooth production of the blast furnace. Therefore, the performance requirements are stringent. The present invention uses tungsten atoms coated with nano silicon carbide and other antioxidants to prepare the Al2O3-SiC-C iron ditch castable, which improves the high-temperature oxidation resistance of the castable, increases the service life, and has a good application prospect. The specific mechanism is:

[0029] By adding nano silicon carbide, the high temperature oxidation resistance is significantly improved by utilizing the characteristics of nano silicon carbide powder, such as high purity, small particle size distribution range, high specific surface area, stable chemical properties, high thermal conductivity, small thermal expansion coefficient, and good wear resistance. However, nano silicon carbide is easy to agglomerate, and it is not easy to disperse after agglomeration. The SiO2 generated after high temperature oxidation is locally aggregated, and it is easy to react with CaO in the material to form low melting products, thereby reducing the high temperature performance of the material. The present invention utilizes atomic assembly technology to coat a layer of tungsten atoms on the surface of nano silicon carbide powder, construct a highly active interface of nano silicon carbide powder, improve its high temperature interface sintering activity, and avoid the agglomeration of nano SiC micropowder. The specific mechanism is: high surface-interface activity can not only effectively remove oxygen pollution on the surface of ceramic powder, but also accelerate the transfer and diffusion of metal and non-metal elements, and reduce the liquid phase generation temperature; the low temperature passivation layer on the surface of the carbonyl metal after coating can reduce the binding free energy of powder agglomeration, thereby avoiding the agglomeration of nano powder.

[0030] At the same time, refractory metal tungsten has good ductility and is one of the ideal sintering aids for high-temperature materials. As a sintering aid, refractory metal tungsten has the following advantages: it can effectively relieve thermal stress and reduce the impact of thermal stress on materials, such as delaying or preventing the expansion of cracks; atomic-scale tungsten can effectively reduce its own sintering melting point; excellent high-temperature resistance and high melting point can ensure that the use temperature of ultra-high temperature composite materials is not affected; it can improve the structure of the oxide layer, form a WO3-SiO2 composite protective layer, and improve the density of the oxide layer above 1400°C, thereby improving the high-temperature oxidation resistance of the castable.

[0031] In addition, in combination with composite antioxidants, the oxygen content in the castable is consumed first at the medium and low temperature stages, generating some oxides to block the pores, thereby increasing the density of the castable and hindering the entry of external oxygen, thereby jointly improving the castable's antioxidant properties.

[0032] The beneficial effects of the present invention are as follows:

[0033] 1. The present invention provides a highly antioxidant Al2O3-SiC-C iron ditch castable, which adopts tungsten atoms to coat nano silicon carbide, synergistic composite antioxidants, and other components to achieve improved oxidation resistance in a temperature range above 1400°C, significantly improve the high-temperature slag corrosion resistance and erosion resistance of the castable, and has broad application prospects.

[0034] 2. Furthermore, tungsten atom-coated nano-silicon carbide is pre-mixed with a composite antioxidant, and the tungsten element is used to reduce the thermal stress between SiC and ZrB2, thereby increasing the viscosity and density of the oxide layer, and obtaining an Al2O3-SiC-C quality iron ditch castable with high fracture toughness and excellent high-temperature oxidation resistance.

[0035] 3. The preparation method of the present invention is simple and is conducive to industrial promotion and application. DETAILED DESCRIPTION

[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] In the embodiment of the present invention, a highly antioxidant Al2O3-SiC-C quality iron ditch castable is provided. The raw materials include, by weight: 45-65 parts of fused brown corundum, 10-20 parts of fused dense corundum, 12-18 parts of silicon carbide, 5-8 parts of activated alumina powder, 1-2 parts of cement, 1.5-2.5 parts of silicon dioxide powder, 1-3 parts of tungsten atom-coated nano-silicon carbide, 1-3 parts of carbon material, 1-2 parts of metallic silicon powder, 1-2 parts of composite explosion-proof agent, 0.2-0.4 parts of composite antioxidant, and 0.1-0.2 parts of composite water reducer.

[0038] In a specific embodiment, the raw material indexes are as follows:

[0039] The fused brown corundum consists of a part with a particle size of 8-5 mm, a part with a particle size of 5-3 mm, and a part with a particle size of 3-1 mm, and the mass ratios thereof are 40-50%, 25-30%, and 25-30% respectively.

[0040] The fused dense corundum consists of a part with a particle size of 1 to 0.074 mm and a part with a particle size of ≤0.074 mm, and the mass ratios of the two parts are 50 to 60% and 40 to 50% respectively.

[0041] The silicon carbide 0-1mm consists of a part with a particle size of 1 to 0.074mm and a part with a particle size of ≤0.074mm, wherein the mass proportions of the part with a particle size of 1 to 0.074mm and the part with a particle size of ≤0.074mm are 45 to 55% and 45 to 55% respectively.

[0042] The activated alumina powder 50 ≤2μm, Al2O3≥99%.

[0043] The cement is pure calcium aluminate cement, wherein Al2O3≥68%.

[0044] The silicon dioxide fine powder has d50≤5μm and SiO2≥96%.

[0045] The tungsten atom-coated nano-silicon carbide uses hexacarbonyl tungsten powder as a precursor, and utilizes chemical vapor deposition to coat atomic tungsten on the surface of SiC powder to obtain atomic tungsten-coated SiC porcelain powder; wherein the tungsten atom-coated nano-silicon carbide has a silicon carbide particle size of 400 to 600 nm and a tungsten atom coating layer thickness of 100 to 200 nm.

[0046] The carbon material is one of spherical pitch and carbon black or a mixture of the two.

[0047] The metal silicon powder has a particle size of ≤0.44 μm and a silicon content of ≥98%.

[0048] The composite explosion-proof agent is a mixture of two or three of metal aluminum powder, aluminum lactate, and explosion-proof fibers; wherein the explosion-proof fibers are polypropylene fibers with a length of 2-4 mm.

[0049] The composite antioxidant comprises boron carbide and zirconium boride.

[0050] The composite water reducer is a mixture of two or three of sodium tripolyphosphate, FDN (sodium polymethylene naphthalene sulfonate) and polycarboxylic acid high-efficiency water reducer.

[0051] In the embodiment of the present invention, the iron hook casting material is prepared by the following steps:

[0052] 1) Weigh tungsten atom-coated nano-silicon carbide powder and composite antioxidant respectively, put them into polyethylene glycol solution for electromagnetic stirring to obtain mixed slurry; and obtain dry mixed powder by vacuum spray drying.

[0053] 2) Weigh fused brown corundum, fused dense corundum, silicon carbide, activated alumina powder, cement, silicon dioxide powder, carbon material, metallic silicon powder, composite explosion-proof agent, composite water reducing agent and the mixed powder obtained in step 1) by weight, put them into a forced mixer and stir for 20 minutes to obtain a highly antioxidant Al2O3-SiC-C iron ditch castable.

[0054] The specific embodiments of the present invention are as follows:

[0055] Example 1

[0056] Provided is a highly oxidation resistant Al2O3-SiC-C quality iron ditch castable, which comprises, by weight:

[0057] 45 parts by mass of fused brown corundum, 20 parts by mass of fused dense corundum, 16 parts by mass of silicon carbide 0-1mm, 7 parts by mass of activated alumina powder, 2 parts by mass of cement, 1.5 parts by mass of silicon dioxide powder, 2.5 parts by mass of tungsten atom-coated nano-silicon carbide, 3 parts by mass of carbon material (the mass ratio of ball pitch to carbon black is 2:1), 2 parts by mass of metallic silicon powder, 1 part by mass of composite explosion-proof agent (the mass ratio of metallic aluminum powder, aluminum lactate and explosion-proof fiber is 1:1:1), 0.4 parts by mass of composite antioxidant (the mass ratio of boron carbide and zirconium boride is 1:2), and 0.2 parts by mass of composite water reducer (the mass ratio of sodium tripolyphosphate, FDN and polycarboxylic acid high-efficiency water reducer is 1:2:1).

[0058] The specific performance test of the environmentally friendly and corrosion-resistant iron ditch castable obtained in this embodiment is shown in Table 1.

[0059] Table 1. Product performance indicators

[0060]

[0061]

[0062] Example 2

[0063] Provided is a highly oxidation resistant Al2O3-SiC-C quality iron ditch castable, which comprises, by weight:

[0064] 50 parts by mass of fused brown corundum, 18 parts by mass of fused dense corundum, 18 parts by mass of silicon carbide 0-1mm, 5 parts by mass of activated alumina powder, 2 parts by mass of cement, 2 parts by mass of silicon dioxide powder, 1 part by mass of tungsten atom-coated nano silicon carbide, 2 parts by mass of carbon material (the mass ratio of ball pitch to carbon black is 1:1), 1 part by mass of metal silicon powder, 1 part by mass of composite explosion-proof agent (the mass ratio of metal aluminum powder, aluminum lactate and explosion-proof fiber is 2:1:1), 0.2 parts by mass of composite antioxidant (the mass ratio of boron carbide and zirconium boride is 1:1), 0.2 parts by mass of composite water reducer (the mass ratio of FDN and polycarboxylic acid high-efficiency water reducer is 1:2)

[0065] The specific performance test of the environmentally friendly and corrosion-resistant iron ditch castable obtained in this embodiment is shown in Table 2.

[0066] Table 2. Product performance indicators

[0067]

[0068] Example 3

[0069] Provided is a highly oxidation resistant Al2O3-SiC-C quality iron ditch castable, which comprises, by weight:

[0070] 55 parts by mass of fused brown corundum, 15 parts by mass of fused dense corundum, 14 parts by mass of silicon carbide 0-1mm, 6 parts by mass of activated alumina powder, 1 part by mass of cement, 1.5 parts by mass of silicon dioxide powder, 2 parts by mass of tungsten atom-coated nano-silicon carbide, 2 parts by mass of carbon material (the mass ratio of ball pitch to carbon black is 3:1), 1.5 parts by mass of metallic silicon powder, 2 parts by mass of composite explosion-proof agent (the mass ratio of metallic aluminum powder, aluminum lactate and explosion-proof fiber is 1:1:1), 0.3 parts by mass of composite antioxidant (the mass ratio of boron carbide and zirconium boride is 2:1), and 0.2 parts by mass of composite water reducer (the mass ratio of sodium tripolyphosphate, FDN and polycarboxylic acid high-efficiency water reducer is 1:1:1).

[0071] The specific performance test of the environmentally friendly and corrosion-resistant iron ditch castable obtained in this embodiment is shown in Table 3.

[0072] Table 3. Product performance indicators

[0073]

[0074] Example 4

[0075] Provided is a highly oxidation resistant Al2O3-SiC-C quality iron ditch castable, which comprises, by weight:

[0076] 58 parts by mass of fused brown corundum, 11 parts by mass of fused dense corundum, 14 parts by mass of silicon carbide 0-1mm, 6 parts by mass of activated alumina powder, 2 parts by mass of cement, 2 parts by mass of silica powder, 2.5 parts by mass of tungsten atom-coated nano silicon carbide, 1.5 parts by mass of carbon material (the mass ratio of ball pitch to carbon black is 4:1), 2 parts by mass of metallic silicon powder, 1 part by mass of composite explosion-proof agent (the mass ratio of metallic aluminum powder, aluminum lactate and explosion-proof fiber is 2:1:1), 0.2 parts by mass of composite antioxidant (the mass ratio of boron carbide and zirconium boride is 1:3), and 0.1 parts by mass of composite water reducer (the mass ratio of sodium tripolyphosphate and polycarboxylic acid high-efficiency water reducer is 1:2).

[0077] The specific performance test of the environmentally friendly and corrosion-resistant iron ditch castable obtained in this embodiment is shown in Table 4.

[0078] Table 4. Product performance indicators

[0079]

[0080]

[0081] Example 5

[0082] Provided is a highly oxidation resistant Al2O3-SiC-C quality iron ditch castable, which comprises, by weight:

[0083] 62 parts by mass of fused brown corundum, 10 parts by mass of fused dense corundum, 13 parts by mass of silicon carbide 0-1mm, 7 parts by mass of activated alumina powder, 1 part by mass of cement, 2 parts by mass of silicon dioxide powder, 1 part by mass of tungsten atom-coated nano silicon carbide, 1 part by mass of carbon material (the mass ratio of ball pitch to carbon black is 1:1), 1 part by mass of metal silicon powder, 2 parts by mass of composite explosion-proof agent (the mass ratio of metal aluminum powder, aluminum lactate and explosion-proof fiber is 1:2:1), 0.4 parts by mass of composite antioxidant (the mass ratio of boron carbide and zirconium boride is 1:1), 0.2 parts by mass of composite water reducer (the mass ratio of sodium tripolyphosphate, FDN and polycarboxylic acid high-efficiency water reducer is 1:1:2)

[0084] The specific performance test of the environmentally friendly and corrosion-resistant iron ditch castable obtained in this embodiment is shown in Table 5.

[0085] Table 5. Product performance indicators

[0086]

[0087] The performance test reference standards in all embodiments are as follows:

[0088] Test the apparent porosity and bulk density of the sample according to GB / T2997-2015;

[0089] According to GB / T5072-2008 test sample's room temperature compressive strength;

[0090] According to GB / T3001-2017 test sample room temperature flexural strength;

[0091] According to GB / T3002-2017 test sample's high temperature flexural strength;

[0092] Test the sample line change rate according to GB / T5988-2022;

[0093] The slag resistance of the test sample is tested according to GB / T8931-2007.

[0094] It can be seen from the performance data of the embodiments shown in Tables 1-5 that the castable has good high-temperature oxide layer thickness and anti-corrosion and anti-penetration properties.

[0095] The above embodiments are intended to illustrate the present invention, not to limit the present invention. Any solution that is a simple transformation of the present invention belongs to the protection scope of the present invention.

Claims

1. A highly oxidation resistant Al2O3-SiC-C iron ditch castable, characterized in that: Calculated by weight, it includes 45-65 parts of fused brown corundum, 10-20 parts of fused dense corundum, 12-18 parts of silicon carbide 0-1mm, 5-8 parts of activated alumina powder, 1-2 parts of cement, 1.5-2.5 parts of silicon dioxide powder, 1-3 parts of tungsten atom-coated nano silicon carbide, 1-3 parts of carbon material, 1-2 parts of metallic silicon powder, 1-2 parts of composite explosion-proof agent, 0.2-0.4 parts of composite antioxidant and 0.1-0.2 parts of composite water reducer.

2. The iron trough castable according to claim 1, characterized in that: The tungsten atom-coated nano-silicon carbide uses hexacarbonyl tungsten powder as a precursor, and utilizes a chemical vapor deposition method to coat atomic tungsten on the surface of SiC powder to obtain atomic tungsten-coated SiC powder.

3. The iron trough castable according to claim 1 or 2, characterized in that: In the tungsten atom-coated nano-silicon carbide, the silicon carbide particle size is 400-600nm, and the tungsten atom coating layer thickness is 100-200nm.

4. The iron trough castable according to claim 1, characterized in that: The fused brown corundum consists of a part with a particle size of 8-5mm, a part with a particle size of 5-3mm, and a part with a particle size of 3-1mm, and the mass ratios thereof are 40-50%, 25-30%, and 25-30% respectively; the fused dense corundum consists of a part with a particle size of 1-0.074mm and a part with a particle size ≤0.074mm, and the mass ratios thereof are 50-60% and 40-50% respectively.

5. The iron trough castable according to claim 1, characterized in that: The silicon carbide 0-1mm consists of a part with a particle size of 1 to 0.074mm and a part with a particle size of ≤0.074mm, wherein the mass proportions of the part with a particle size of 1 to 0.074mm and the part with a particle size of ≤0.074mm are 45 to 55% and 45 to 55% respectively.

6. The iron trough castable according to claim 1, characterized in that: The activated alumina powder 50 ≤2μm, Al2O3≥99%; the silicon dioxide powder d50≤5μm, SiO2≥96%; the metal silicon powder particle size ≤0.44μm, silicon content ≥98%.

7. The iron trough castable according to claim 1, characterized in that: The cement is pure calcium aluminate cement, wherein Al2O3≥68%; the carbon material is spherical asphalt, carbon black or a mixture of the two.

8. The iron trough castable according to claim 1, characterized in that: The composite explosion-proof agent includes two or three of metal aluminum powder, aluminum lactate, and explosion-proof fiber; the composite antioxidant includes boron carbide and zirconium boride; the composite water reducer includes two or three of sodium tripolyphosphate, FDN, and polycarboxylic acid high-efficiency water reducer.

9. The iron trough castable according to claim 1, characterized in that: The iron trough casting is prepared by adding tungsten atom-coated nano silicon carbide powder and composite antioxidant into polyethylene glycol solution to obtain mixed slurry, vacuum spray drying to obtain mixed powder, and then mixing with other remaining components.

10. A method for preparing the highly oxidation resistant Al2O3-SiC-C iron tapping trough castable according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) Adding tungsten atom-coated nano silicon carbide powder and composite antioxidant into polyethylene glycol solution and stirring to obtain mixed slurry; and then vacuum spray drying to obtain mixed powder. 2) Mix fused brown corundum, fused dense corundum, silicon carbide, activated alumina powder, cement, silicon dioxide powder, carbon material, metallic silicon powder, composite explosion-proof agent, composite water reducing agent and the mixed powder obtained in step 1), and stir evenly to obtain a highly antioxidant Al2O3-SiC-C quality iron ditch castable.

Citation Information

Patent Citations

  • Environment-friendly high-strength anti-oxidation permeation castable for tapping channel and preparation method thereof

    CN111087230A

  • Antioxidant blast furnace iron runner castable and preparation method thereof

    CN117247272A

  • Iron runner castable for large- and medium-sized blast furnaces

    CN109836138A

  • Castable containing nano-alumina and used for blast furnace tapping channel and preparation method thereof

    CN110723963A

  • Preparation method of high-performance ZrB2-SiC ultrahigh-temperature ceramic for aerospace

    CN117417192A